Epidemiology, pathology and identification of Colletotrichum including a novel species associated with avocado (Persea americana) anthracnose in Israel. Issue 1 (December 2017) - Sharma, Gunjan; Maymon, Marcel; Freeman, Stanley
Abstract Anthracnose disease caused byColletotrichum species is a major constraint for the shelf-life and marketability of avocado fruits. To date, onlyC .gloeosporioides sensu lato andC .aenigma have been reported as pathogens affecting avocado in Israel. This study was conducted to identify and characterizeColletotrichum species associated with avocado anthracnose and to determine their survival on different host-structures in Israel. The pathogen survived and over-wintered mainly on fresh and dry leaves, as well as fresh twigs in the orchard. A collection of 538Colletotrichum isolates used in this study was initially characterized based on morphology and banding patterns generated according to arbitrarily primed PCR to assess the genetic diversity of the fungal populations. Thereafter, based on multi-locus phylogenetic analyses involving combinations of ITS, act, ApMat, cal, chs1, gapdh, gs, his3, tub 2 gene/markers; eight previously described species (C .aenigma, C .alienum, C .fructicola, C .gloeosporioides sensu stricto, C .karstii, C .nupharicola, C .siamense, C .theobromicola ) and a novel species (C .perseae ) were identified, as avocado anthracnose pathogens in Israel; and reconfirmed after pathogenicity assays.Colletotrichum perseae sp. nov. and teleomorph ofC .aenigma are described along with comprehensive morphological descriptions and illustrations, for the first time in this study.